2011
DOI: 10.1073/pnas.1107898108
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone synthesis bypasses testosterone to drive castration-resistant prostate cancer

Abstract: In the majority of cases, advanced prostate cancer responds initially to androgen deprivation therapy by depletion of gonadal testosterone. The response is usually transient, and metastatic tumors almost invariably eventually progress as castration-resistant prostate cancer (CRPC). The development of CRPC is dependent upon the intratumoral generation of the potent androgen, dihydrotestosterone (DHT), from adrenal precursor steroids. Progression to CRPC is accompanied by increased expression of steroid-5α-reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
289
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(302 citation statements)
references
References 33 publications
(39 reference statements)
7
289
1
4
Order By: Relevance
“…The Physicians' Health Study confirmed the starting hypothesis, namely that testosterone and dihydrotestosterone (DHT) were positively associated with estradiol, and that sex hormone binding globulin was inversely associated with prostate cancer (Gann PH et al 1996). In recent years, several clinical studies of hormone treatment for prostate cancer have been done (Cai C et al 2011;Chang KH et al 2011;Mostaghel EA et al 2011;Richards J et al 2012;Mostaghel EA 2013). Prostate-specific antigen (PSA) is a glycoprotein produced almost exclusively by the epithelial cells of the prostate gland, and is used as a marker for the diagnosis and monitoring of prostate cancer (Hudson MA et al 1989;Oesterling JE 1991;Armbruster DA 1993).…”
Section: Introductionmentioning
confidence: 80%
“…The Physicians' Health Study confirmed the starting hypothesis, namely that testosterone and dihydrotestosterone (DHT) were positively associated with estradiol, and that sex hormone binding globulin was inversely associated with prostate cancer (Gann PH et al 1996). In recent years, several clinical studies of hormone treatment for prostate cancer have been done (Cai C et al 2011;Chang KH et al 2011;Mostaghel EA et al 2011;Richards J et al 2012;Mostaghel EA 2013). Prostate-specific antigen (PSA) is a glycoprotein produced almost exclusively by the epithelial cells of the prostate gland, and is used as a marker for the diagnosis and monitoring of prostate cancer (Hudson MA et al 1989;Oesterling JE 1991;Armbruster DA 1993).…”
Section: Introductionmentioning
confidence: 80%
“…3β-HSD is expressed in the normal human prostate, with immunoblotting revealing that the highest concentrations are found in basal epithelial cells (Luu-The et al 2008). Certainly, in mouse xenograft studies using the CRPC LAPC4 cell line, expression of 3β-HSD is increased within the tumour in addition to AKR1C3 and 17β-HSD3 (Chang et al 2011), although its mRNA expression almost completely mutually excludes that of CYP19A1 (Hofland et al 2010).…”
Section: :6mentioning
confidence: 99%
“…Mass spectrometry has shown that even in patients on anti-androgen therapy with very low serum testosterone levels, intra-tumoural DHT concentrations remain at the pre-treatment level (Chang et al 2011. 17β-HSD-5, also known as AKR1C3, appears to be the key enzyme responsible for intra-tumoural androgen production in CRPC.…”
Section: :6mentioning
confidence: 99%
“…E 1 ) to highly active 17b-steroids (e.g. E 2 ), and vice versa, has also become apparent, and the enzymes are expected to be involved in the local production of both classical and novel ligands for ERs in several normal and diseased tissues (for example, Chang et al 2011, Mohler et al 2011, Saijo et al 2011, Saloniemi et al 2012. It is thus likely that yet unknown endogenous small molecular compounds modulating ERs are to be discovered in the future.…”
mentioning
confidence: 99%